Correlation between the Degree of Psychological Stress with Pain Intensity in Tension-Type Headache Patients - Pambudi, Pagan; Sidabutar, Oktaviana (Fakultas Kedokteran Universitas Brawijaya, 2024)
Tension-Type Headache (TTH) is a critical health problem, particularly in Indonesia, with psychological stress being the most recognized contributing factor. The mechanism by which stress contributes to TTH is not fully understood, but stress has been found to increase pain sensitivity in peripheral or central patients with TTH, alongside the influence of biopsychosocial factors in different individuals. Therefore, this study aimed to analyze the relationship between the degree of psychological stress and pain intensity in patients with TTH at Dr. H. Moch Ansari Saleh Banjarmasin General Hospital. This observational analytic study was carried out using a cross-sectional approach and the 30 samples employed were taken through a systematic random sampling technique. The data was analyzed using Spearman's test. Our result showed that 63.33% of patients had mild stress, while 36.67% were moderate. In the mild stress group, there were 15.79% mild pain, 73.68% moderate pain, and 10.53% severe pain. Meanwhile, in the moderate stress group, 72.73% reported moderate pain, and 27.27% had severe pain. In conclusion, this study indicated there was a correlation between the degree of psychological stress and the intensity of pain in TTH patients, despite not statistically significant (p=0.102 and R=0.304).